Change in agitation in Alzheimer's disease in the placebo arm of a nine-week controlled trial. (25th August 2015) - Rosenberg, Paul B.; Drye, Lea T.; Porsteinsson, Anton P.; Pollock, Bruce G.; Devanand, D.P.; Frangakis, Constantine; Ismail, Zahinoor; Marano, Christopher; Meinert, Curtis L.; Mintzer, Jacobo E.; Munro, Cynthia A.; Pelton, Gregory; et al.
ABSTRACT: Background: Placebo responses raise significant challenges for the design of clinical trials. We report changes in agitation outcomes in the placebo arm of a recent trial of citalopram for agitation in Alzheimer's disease (CitAD). Methods: In the CitAD study, all participants and caregivers received a psychosocial intervention and 92 were assigned to placebo for nine weeks. Outcomes included Neurobehavioral Rating Scale agitation subscale (NBRS-A), modified AD Cooperative Study-Clinical Global Impression of Change (CGIC), Cohen-Mansfield Agitation Inventory (CMAI), the Neuropsychiatric Inventory (NPI) Agitation/Aggression domain (NPI A/A) and Total (NPI-Total) and ADLs. Continuous outcomes were analyzed with mixed-effects modeling and dichotomous outcomes with logistic regression. Results: Agitation outcomes improved over nine weeks: NBRS-A mean (SD) decreased from 7.8 (3.0) at baseline to 5.4 (3.2), CMAI from 28.7 (6.7) to 26.7 (7.4), NPI A/A from 8.0 (2.4) to 4.9 (3.8), and NPI-Total from 37.3 (17.7) to 28.4 (22.1). The proportion of CGI-C agitation responders ranged from 21 to 29% and was significantly different from zero. MMSE improved from 14.4 (6.9) to 15.7 (7.2) and ADLs similarly improved. Most of the improvement was observed by three weeks and was sustained through nine weeks. The major predictor of improvement in each agitation measure was a higher baseline score in that measure. Conclusions: We observed significant placebo response which may be due to regression to the mean, response to a psychosocial intervention, natural course of symptoms, or nonspecific benefits of participation in a trial.